Gabay sa tagapagsanay ng mga legal advocates sa komunidad - Ealdama, Yolanda G.; Rago , Lucia Cynita C.; Pecimo, Shella O. (Women's Legal Bureau, 1998)
Guidebook for trainer of legal advocates in Philippines community.